PHYTOGEOGRAPHY AND FLORISTICS OF THE ARBOR COMPONENT IN UNIÃO DO VEGETAL TERRITORIES INTENDED FOR THE CULTIVATION OF BANISTERIOPSIS CAAPI AND PSYCHOTRIA VIRIDIS IN RONDÔNIA - Thevenin, Julien Marius Reis; Sambuichi, Regina Helena Rosa (Ra'e Ga: o Espaço Geográfico em Análise, 2020)
The territorial expansion of Amazonian religions that make ritual use of Ayahuasca / Hoasca, in Rondônia, has been associated to the maintenance of forested areas and recovery of degraded areas associated with the cultivation of Banisteriopsis caapi [(SpruceexGriseb.) CV Morton] and Psychotria viridis (Ruiz & Pav.) in agroforestry systems (SAFs). The present research had as objective to carry out the floristic survey and to analyze the composition and structure of the arboreal component of the forest fragments and agroforestry of territorial areas of União do Vegetal, one of the Hoasca religious matrices, in each phytoecological region of its comprehension in Rondônia. For this, non-probabilistic samples were performed on 08 rural properties in the delimited territory. In the selected areas, disjoint plots of 50 x 20 m (0.1 ha) were plotted, totaling 23 plots and 2.3 ha of area sampled, and then phytosociological parameters were calculated in the FITOPAC 2.1 application. Floristic surveys and phytosociological parameters presented satisfactory results regarding the conservation of phytodiversity in these areas according to the phytoecological region in which they are found. The occurrence of species in the Near Threatened and Vulnerable (VU) status by RedList shows the importance of these territories to conservation. In the case of samples in cultivated areas of the ritual species, these results were superior to other Agroforestry Systems, and in 75% of the samples better than the own areas of forest destined to the Legal Reserve of the same property.